EFFECTS OF MORAL DISTRESS ON NURSES: INTEGRATIVE LITERATURE REVIEW - Flavia Regina Ramos; Priscila Orlandi Barth; Ana Maria Masiel Schneider; Amanda Santos Cabral; Jéssica da Silva Reinaldo (Universidade Federal do Paraná, 2016)
The present study aimed to identify the effects of moral distress on nurses. Integrative literature review with data collection from May to September 2013 and updated in July 2015 in database Biblioteca Virtual emSaúde, using the terms: Moral Distress, Moral Suffering, Nurse andNursing.The final sample was composed of eighty-five studies.The outcomes are presented in four categories. The first one (Feelings) includes dissatisfaction, frustration and anger; the second (Sickening) emerged from the experience of physical and emotional sickening; the third (Quality of care) concerns the actions that resulted in ineffective care and denial of patient advocacy; and the fourth (Coping Strategies)showed the types of coping such as:abandonment of the profession and denaturalization of the practices. The effects are present in the daily routine of the professionals, causing damage often irreversible and, abandonment of the employment.